Logistics Network Design for Manufacturing Enterprises with Component Processing Workshops - Ding, Yizhong (Wuhan University journal of natural sciences, 2010)
Logistics network design influences the efficiency and cost of Logistics directly.Some manufacturing enterprises not only have warehouse hubs,but also build component processing workshops which are usually located in those places where the costs of materials and workforce are lower.This paper establishes a logistics network design model for the manufacturing enterprises with component processing workshops based on 0-1 mixture integer programming.The model optimizes the logistics network in an integrated view,by which the selection of the nodes,the manufacturing plan,and transportation plan can be obtained.An example is given to verify its feasibility.The approach is helpful for designing of the logistics network in manufacturing enterprises.